Zur Geschichte der Reedereigebaude an der Elbstrase bei der Alten Liebe in Cuxhaven seit den 1920er Jahren - Gleitsmann-Topp, Rolf-Jurgen (Technikdiskurse. Karlsruher Studien zur Technikgeschichte, 2020)
This study will discuss the history of the creation, construction and use of three distinctive shipping company villas in the harbour of Cuxhaven/Germany, located south of the harbours lighthouse, near the Alte Liebe". The study´s analysis does not however limit itself only to aspects of a historiography of bildings, but rather combines these with a historical approach that contextualize the review undertaken . Lastly the study deleves into the motives and strategies of the involved protagonists and illuminate the results of their activities.